GENDER BIAS IN METHODOLOGICAL NEUTRALITY: CRITIQUE AND ALTERNATIVES FROM A FEMINIST PERSPECTIVE - Palupi, Anggi Trivina (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study aims to critique the claim of neutrality in qualitative social research methodologies, which have long been considered objective and value-free. Through a feminist epistemological approach, this research demonstrates that the claim of objectivity often conceals masculine dominance and power relations in the construction of scientific knowledge. Using a descriptive qualitative method and a critical discourse analysis approach along with feminist reflection, this study analyzes literature and case studies that represent gender bias in social research design. The findings indicate that conventional methodologies tend to overlook the complexity of women's experiences and other marginalized groups. In response to this, the study proposes alternative, more gender-inclusive qualitative methodologies, such as gender-sensitive interviews, feminist autoethnography, and reflective narrative methods, which allow for more equitable representation in the knowledge production process. Findings reveal gender bias in research that neglects women’s perspectives, alongside three proposed inclusive methodologies to address this imbalance.